Nursing workload in mental health - Sidnei Roberto Alves; Reginaldo Passoni dos Santos; Régio Marcio Toesca Gimenes; Mirian Ueda Yamaguchi (Rev Rene)
Objective: to compare the workload in nursing mental health professionals who work in the public service and the private service. Methods: this is a quantitative research conducted with 70 nursing professionals in two services. For data collection, the evaluation scale of the work impact on mental health services was applied. Results: in the overall analysis, there was no statistically significant difference in the average score for workload among professionals of both institutions. However, all subscale averages had statistical differences, and the subscale “emotional repercussions at work” showed the highest significance. Conclusion: the nursing staff from the private service had higher workload average.